Solving Logarithmic Equation @KasyannoEZMath

preview_player
Показать описание
In this video, you'll learn how to solve the given logarithmic equation.
Рекомендации по теме
Комментарии
Автор

... Good day, Given: LOG(base 2)(X - 6) = LOG(base 4)(4X - 3) ... LN(X - 6)/LN(2) = LN(4X - 3)/LN(4) [ LN(4) = 2LN(2) ] ... 2LN(X - 6)/LN(2) = LN(4X - 3)/LN(2) [ 2LN(X - 6) = LN((X - 6)^2) ] ... (X - 6)^2 = 4X - 3 ... X^2 - 12X + 36 = 4X - 3 ... X^2 - 16X + 39 = 0 ... (X - 3)(X - 13) = 0 ... X1 = 3 v X2 = 13 [ The candidate solution X1 delivers a negative argument of LOG(base 2)( ... ) on the left side of the original equation, so X1 cannot be a solution ] ... The candidate solution X2 = 13 satisfies the original equation, so X2 = 13 is the solution of your given equation ... S = { 13 } ... Thank you for your clear solution strategy and take care, Jan-W

jan-willemreens